(untitled) (Scientific journal of the Fergana State University, 2023)
By providing sulfocationite obtained on the basis of polyvinyl chloride, which is a local raw material, new ionizing materials containing both cation-exchange sulfogroup and anion-exchange amino groups were obtained. Absorption kinetics and isotherms of iodine ions in aqueous solutions were calculated for the obtained ion-carrying material under static conditions.